Classification of modules of dimension $n$ and multiplicity 1 over the Weyl algebra $A_n$ - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
Modules of the Gelfand - Kirillov dimension $n$ and the multiplicity 1 over the Weyl algebra $A_n$ are classified.